Comparative Advantage, Terms of Trade and Welfare Effects of European Integration: Some Preliminary Assessments - Jan I. Haaland (The Research Institute of Industrial Economics (IUI), 1990)
The paper presents a first attempt at assessing general equilibrium effects of 1992. Two kinds of general equilibrium effects are relevant: one (dampening) effect stemming from the common resource constraints, the other one related to the fact that the relative competitiveness of industries may be altered as a consequence of the integration. This paper focuses on the second type of general equilibrium effects, and the results show that there may be additional gains for the EC stemming from terms-of-trade improvements and reduced dependence on subsidized and protected industries. The paper also presents general equilibrium assessments for Norway, under various assumptions regarding Norwegian participation in the integration process.
Keywords: F12; F15; I31; 330; Economic integration; Welfare; Trade